Constructivism of Awig-Awig in Maintaining the Authenticity of Tista Traditional Village, Sukasada District, Buleleng Regency - I Wayan Gede, Wisnu; Ida Ayu Putu, Purnami; Ni Putu Diana, Sari (Bina Nusantara University, 2024)
The research aimed to describe the substance and correlation of the Awig-Awig of Tista Traditional Village, Sukasada District, Buleleng Regency, in maintaining authenticity as a collective identity. It examined the villagers’ sociological ability to transmit genealogical and communal ideology. The sociological expressiveness of Tista Traditional Village reflected collective constructivism, distinguishing it as an old village with a unique structural typology rarely found in other traditional Balinese villages, including those categorized as Bali Aga. The research employed a structured methodology, including (1) research design, (2) data types, (3) data collection methods with key and supporting informants, and (4) data analysis methods. The results show that the Awig-Awig of Tista Traditional Village encompasses ideological, sociological, and cosmological aspects. Its correlation includes continuity, diversity, and the potential of Awig-Awig to preserve communal identity over time. The research uncovers the unique structural typology of the Tista Traditional Village, which has not been widely studied. It also analyzes how Awig-Awig sustains the village’s authenticity. It provides new insights into the resilience of traditional governance systems in Bali and their role in maintaining social cohesion and cultural heritage. The findings contribute to expanding knowledge about the authenticity and identity of traditional Balinese villages, particularly regarding the role of Awig-Awig.